Aspectos clínicos e laboratoriais da histiocitose das células de Langerhans: Estudo retrospectivo no hospital das clinicas da UFMG 1988 a 2004 - Marcia Kanadani Campos (2005)
Objectives: Describe the clinical presentation of Langerhans Cell Histiocytosis (LCH) and compare the illness outcome in relation to age, sex, staging and treatment. Methods: Retrospective data from 33 children with LCH, diagnosed at Hospital of Clinics, Federal University of Minas Gerais from 1998 to 2004 were analyzed. Results: The age at diagnosis ranged from 2 months to 16 years. There were 17 males. The observation period ranged from 21 days to 16.2 years (median of 3.4 years). Bone, lymph nodes and skin lesions were the most frequent manifestations at diagnosis. The estimated overall survival (OS) probability was 86.1% at 16 years (95% confidence interval: 66.6% to 94.6%). All deaths occurred in children with multisystemic disease andorgan dysfunction at diagnosis. OS was higher for patients who were better after 6 weeks of initial therapy. The OS probability was significantly higher for those patients with single-system disease. The probability of event-free survival (EFS) at 16 years survival was 30.9% (95% confidence interval: 15.6% to 47.5%); it was significantly higher forthose patients with single-system disease. Age, gender and treatment were not significantly associated with EFS. Diabetes insipidus was reported in 21% of patients and was the most common sequela. No secondary malignancy was observed. Conclusion: The clinical manifestations of Langerhans Cell Histiocytosis vary widely. Although the mortality rate is low, disease reactivation is almost the rule.